Heat loss of fertile eggs on the road between the hatchery and hatcher - Da Silva, Gabriela Fagundes [UNESP]; Pereira, Danilo Florentino [UNESP] (American Society of Agricultural and Biological Engineers (ASABE), 2016)
The microenvironment around the fertile egg on incubation process can influence the development of the embryo and reflect on the hatching rate in the post-hatching performance, and also the quality of the hatched chicks. Thus, the temperature control during the incubation process, which includes everything, from the arrival of the eggs in the waiting room, passing the hatchery, candling and hatcher is essential for the proper development of the embryo. However, it is observed that in Brazilian incubatories the paths made in the transfer of eggs between the hatcheries and hatchers, the thermal environment is not controlled, which can cause heat loss of eggs to the environment. This research aimed at accurately monitor heat loss of fertile eggs. The experiment was conducted in a commercial incubatory located in São Paulo, Brazil. The experimental design was completely randomized in a factorial scheme 3×2, consisting of three ages of broiler breeders (26, 32 and 53 weeks) and two transport treatments of eggs, and the same treatment as adopted by the company in carts without thermal insulation (T0) and other in boxes with thermal insulation (T1). It was used a total of 1728 eggs divided into three replications. It was recorded and analyzed 36 thermographic images of egg trays at the time of removal from the hatchery and at the time of arrival at the hatcher, and in this way the eggs were subjected to candling in a non-acclimatized room. From the surface temperatures obtained from the thermographic images, it was calculated the total heat loss of the eggs. The total average time of transfer from the hatchery to the hatcher was 10 minutes for both treatments. The results showed that the heat loss of T1 eggs was 0.28 cal lower than T0 eggs. It was concluded that at the process of incubation of fertile eggs in this incubatory there is no need to control the environment in the path of the hatchery and hatcher including the candling room to minimize heat losses of the eggs to the environment, envisioning the possibility of improving hatching rate and quality of born chick.
Keywords: Embryonic development; Thermal control; Thermographic camera; Transfer of fertile eggs